Crosstalk Between Female Gonadal Hormones and Vaginal Microbiota Across Various Phases of Women’s Gynecological Lifecycle - Kaur, Harrisham; Merchant, Mitali; Haque, Mohammed Monzoorul; Mande, Sharmila S. (Frontiers in Microbiology, 2020)
Functional equilibrium between vaginal microbiota and the host is important for maintaining gynaecological and reproductive health. Apart from host genetics, infections, changes in diet, life-style and hygiene status are known to affect this delicate state of equilibrium. More importantly, the gonadal hormones strongly influence the overall structure and function of vaginal microbiota. Several studies have attempted to understand (a) the composition of vaginal microbiota in specific stages of women's reproductive cycle (b) their association with gonadal hormones, and their potential role in manifestation of specific health conditions (from the perspective of cause/ consequence). However, a single study that places, in context, the structural variations of the vaginal microbiome across the entire life-span of women's reproductive cycle is currently lacking. With the objective to obtain a holistic overview of the community dynamics of vaginal micro-environment 'across' various stages of women’s reproductive life-cycle, we have performed a meta-analysis of approximately 1000 vaginal microbiome samples representing various stages of the reproductive cycle. Objectives of this analysis included (a) understanding temporal changes in vaginal community taxonomic structure and composition as women pass through various gynaecological/ reproductive stages (b) exploring correlations between the levels of female sex hormones with vaginal microbiome diversity (c) analysing changes in the pattern of community diversity in cases of infection (i.e. vaginosis) and viewing the analysed changes in the context of a healthy state. Results reveal interesting temporal trends with respect to vaginal microbial community diversity and its pattern of correlation with host physiology. Results indicate significant differences in alpha-diversity and overall vaginal microbial community members in various reproductive phases. In addition to reinforcing the known influence/ role of gonadal hormones in maintaining gynaecological health, results indicate how hormonal level perturbations cause/ contribute to imbalances in the vaginal microbiome. The nature of resulting dysbiotic state and its influence on disease susceptibility is also analysed and discussed. Results also suggest that elevated vaginal microbiome diversity in pregnancy does not necessarily indicate a state of bacterial infection. The study puts forward a hormone-level driven microbiome diversity hypothesis for explaining temporal patterns in vaginal microbiome diversity during various stages of women’s reproductive cycle.